The Effect Of Mild Exercise Induced Dehydration On Sport Concussion Assessment Tool 3 (SCAT3) Scores: A within-subjects design. - Sean M Collins; Monica R Lininger; Thomas G Bowman (International Journal of Sports Physical Therapy)
# Background